Immigrants in Saudi Arabia and Their Demographic-Cultural Impact: A Spatial Analysis Using GIS - Abdelkhalek , Hussein Abdelfattah M.; Alshammri, Amani Rasheed; Alqahtani, Mohammed Ahmed A. (Journal of Posthumanism, 2025)
The Kingdom of Saudi Arabia possesses oil reserves amounting to about 25% of the total reserves in the world, and it is also one of the largest countries attracting immigrants to work in its economic and service sectors. The number of immigrants to the Kingdom has developed from 11.3% of the total population of the state in 1974 to 41.6% according to the 2022 census, with a total number of about 13.4 million people coming from 177 countries around the world. The largest flow of immigrants to work in the Kingdom came from the continent of Asia, from 27 Asian countries, with several 10.2 million immigrants, representing 76.1% of the total immigrants to the Kingdom, according to the 2022 census data. The geographical distribution of foreign immigrants varies across the 13 administrative regions of the Kingdom, with 31% of the total foreigners residing in the Riyadh region, followed by the Makkah region at 28.9%, and then the Eastern Province at 16.3%. These three regions are the highest in terms of the number of economic, urban, and service development projects in the Kingdom, and thus provide attractive job opportunities for immigrants. This geographical distribution of immigrants is reflected in the results of spatial analysis of their distribution using geographic information systems, where the average geographic center point of immigrants in the Kingdom is concentrated west of the Riyadh region in the center of the Kingdom, while 65.4% of the total immigrants in 2022 were concentrated on a standard distance circle covering an area of about 804 thousand km2 in the center of the Kingdom. The analysis of the trend in the distribution of foreign immigrants showed a trend extending from the northeast to the southwest, from the Eastern Province on the Arabian Gulf in the east, passing through the Riyadh region, and reaching the Makkah region located to the west on the Red Sea. This large number of resident immigrants residing in Saudi Arabia has had a clear demographic and cultural impact on the characteristics of the population. For example, the sex ratio of the total population rose to 157.5 males per 100 females in 2022, exceeding the global average of 101 males per 100 females. The population's age structure and population pyramid were also affected, with the proportions of males, especially in the younger age groups, particularly those between 30 and 45 years old. Some cultural and social characteristics of the local population and resident immigrants were also affected, as restaurants serving national foods to immigrants spread, such as Indian, Pakistani, Filipino, Egyptian, and Yemeni restaurants. In addition to the influence on the Arabic language spoken by residents, where some non-Arabic words have entered, hybrid dialects have emerged combining Arabic with words from the languages of these migrants. Meanwhile, the migrants' culture has also been affected.